Specialized imaging and information systems for craniofacial reconstruction - Setan, Halim; Majid, Zulkepli; Suwardhi, Deni (2007)
For specific medical purposes (such as craniofacial reconstruction), human faces and skulls (i.e. soft and hard tissues) need to be modeled and measured accurately. This multi-disciplinary research focuses on the development of surgical planning system for craniofacial reconstruction, for both the soft and hard tissues. The craniofacial reconstruction requires the following: imaging and measurement (non-contact, precise, rapid), 3D models (digital and physical), database, and surgical planner. In this research, the main data are the soft tissue (face) and hard tissue (skull) of craniofacial. This paper discusses the research works undertaken by UTM on the development of specialized imaging system (close range, non-contact, precise, and real time) for capturing soft tissue spatial data, and the development of specialized information system (called MyCIS) for craniofacial applications. The developed real time imaging system combines laser scanning (via MINOLTA VIVID910 scanner) and stereo photogrammetric techniques for acquiring high-resolution 3D models of craniofacial soft tissue. All these 3 types of data (laser scanning, stereo photogrammetric, and CT scan) were processed separately using RAPIDFORM, DVP, and 3DSLICER respectively. MyCIS or Malaysian Craniofacial Information System is developed in-house, and consists of three main components: Data input and pre-processing; Database management; Data analysis and manipulation. MyCIS uses ORDBMS for managing anthropometric/morphometric craniofacial spatial data. MyCIS integrates various inputs (soft tissue from laser scan and photogrammetry, hard tissue from CT-scan, measurement, patient’s information, etc) for managing and visualizing the craniofacial data. The actual results to date (with measurement accuracy of sub-mm) indicate the suitability of the adopted procedure for practical craniofacial applications. This research has produced the latest approach for imaging of soft tissue and managing of local craniofacial database. The results from this research are useful for many multi-disciplinary applications (both local and abroad) requiring craniofacial data.